Closing Now to Reopen Better Tomorrow? Pedagogical Continuity in Latin American Universities During the Pandemic - Francesc Pedró; Débora Ramos Torres (Springer, 2022)
Latin American universities have struggled to ensure pedagogical continuity since the beginning of the pandemic. The objective of this research is to find out how Latin American universities responded to the many challenges posed by their commitment to pedagogical continuity, namely in the technological, pedagogical, financial, and socio-emotional domains, and the support received from their governments. Data was collected through a survey sampling 100 universities in the region covering 16 different countries. The results suggest that many of the challenges faced by universities were more related to the lack of pedagogical skills, from both students and teachers, than to the pitfalls of technological capacity. The survey results are also indicative that the forms of teaching and learning that have begun as emergency formulas to guarantee pedagogical continuity will evolve and consolidate from the time of the reopening, as part of the hybrid model with which we will have to coexist for the time being, and which may become the new pedagogical norm in higher education in the context of a foreseeable restructuring of its provision.